Comparative Study on Renal Function Parameters During Normal Pregnancy and Preeclampsia - Widad A. Hasan (Tikrit Journal of Pure Science, 2019)
Pre-eclampsia is a disease of pregnancy that affects many system in the body, characterized by elevated blood pressure with protein in urine after 20 weeks of pregnancy in pregnant women with no history of hypertension or proteinurea in previous pregnancy. The aim of the current study is to determine the renal function parameters as blood urea and serum creatinine levels in preeclamptic patients and to compare it with the normal pregnant women. This case-control study was conducted among the pregnant women visiting AL-Batool Maternity Teaching Hospital and AL-Khansa Hospital, Mosul, Iraq. Total 150 participants were evaluated out of which 75 were normotensive pregnant women (control group) and 75 were enrolled as preeclamptic group (study group). Serum creatinine and urea levels were measured using standard procedures. Results indicate a significant rise in the mean concentration of serum urea (4.72 ± 1.01 mmol/L vs. 2.48 ± 0.62 mmol/L), serum creatinine (88.8 ± 12.49 µmol / L vs. 56.61 ± 8.2 μmol/L), as compared to that of normotensive pregnant women( P < 0.0001). The findings of the present study are consistent with previous studies, suggesting increased level of serum creatinine and urea in preeclamptic group. Proper history tacking, examination and estimation of serum urea and creatinine may be helpful for management of pre–eclampsia in order to prevent fetal and maternal complications.